(untitled) (Research, Society and Development, 2020)
The aim of this work is to make legislative considerations related to teleworking and the teacher’s activity in distance learning. Over time, different forms of work have been modified. Education is no different. It is a qualitative research, with an approach based on the theoretical framework, as well as on the legal doctrine that covers the topic. As a result, in the Distance Learning modality, teachers are the actors who make the process unfold through the technologies that structure the provision of the service. The period that surrounds us provides a scenario where the relations of this type of service led by the pandemic that has spread worldwide. The working form of teleworking has been the main tool found for the continuity of service provision as a condition for maintaining certain jobs. Within this context, there is the role of the teacher, not only in higher education, but in all forms of teaching. Thus, this area must be governed by the regulations already established in the Collective Labor Convention (CCT), since it governs labor relations in this modality.